The 2016 Lifetime Immunization Schedule, approved by the Italian scientific societies: A new paradigm to promote vaccination at all ages - Paolo Bonanni; Giampietro Chiamenti; Giorgio Conforti; Tommasa Maio; Anna Odone; Rocco Russo; Silvestro Scotti; Carlo Signorelli; Alberto Villani; The Scientific Board of "Lifetime Immunization Schedule" (Taylor & Francis Group, 2017)
Medical scientific societies have the core mission of producing, pooling and disseminating solid and updated scientific information. We report the successful experience of the partnership of four national Medical Scientific Societies active in Italy in producing scientific advice on vaccines and vaccination. In particular, i) the Italian Society of Hygiene, Preventive Medicine and Public Health; SitI, ii) the Italian Society of Paediatrics; SIP, iii) the "Italian Federation of General Practitioners"; FIMP, and iv) the Italian Federation of General Medicine FIMMG) have worked together since 2012 to produce shared evidence-based recommendations on vaccination schedules, namely the "Lifetime Immunization Schedule" which introduced for the first time in Italy a life-course approach to vaccination. The 2014 edition of the "Lifetime Immunization Schedule" was used as a basis to develop the 2017-2019 Italian National Prevention Plan, approved by The Italian Ministry of Health in February 2017. In this report, we present the structure, content and supporting evidence of the new 2016 "Lifetime Immunization Schedule" and we expand on the influential role of medical scientific societies in researching and advocating for effective and safe vaccination programmes' implementation at the national level.